Analisis Pengaruh Rasa Percaya Diri, Motivasi, Dan Skill Terhadap Minat Berwirausaha Pada Mahasiswa STIE Widya Wiwaha - Khatul Hidayah, Afid; Hawa, Iklimatul; Dewi Carneli, Refika; Gita Nanda, Audi; Dani Arifin, Muhammad (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This study aims to analyze the self-confidence, motivation, and skills that affect the interest in entrepreneurship in STIE Widya Wiwaha Yogyakarta students. The population in this study were all students of STIE Widya Wiwaha Yogyakarta. With purposive sampling technique, it means that the sampling method is based on certain considerations that are adjusted to the criteria determined by the researcher which is carried out randomly. Methods the data analysis of this study used multiple regression analysis. The results of this study indicate that partially self-confidence, motivation, and skills have a positive effect on interest in entrepreneurship. The conclusion of this research is that if self-confidence, motivation, and skills are high, it will increase interest in entrepreneurship. This study still has many shortcomings and limitations, this study states that it is a purposive sampling study, meaning that the sampling method is based on certain considerations that are adjusted to the criteria determined by the researcher. In addition, time constraints are also one of the incompleteness of the data so that it cannot be used as a research variable.